The Performance Analysis of Saud Bahwan Group, Oman: An Empirical Study - Alam, Md. Shabbir; Alam, Naushad; Khan, Md Abdul Imran (International Journal of Economics and Financial Issues, 2016)
The present study examines the financial performance Saud Bahawan group vis a vis its competitor and its role in the economic development of Oman. From the empirical work carried out it was established that the ROE has increased over the years from 1350 in 2010 to 14245 in 2014.However on the contrary the net assets to book value, earning per share have declined considerably over the years. The debt ratio has too increased from 0.18 to 0.28 which is a marginal increase and that’s may have attributed to the decline in the EPS. The results showed that, there is no significance different between return on equity of Saud Bahawan and five other companies chosen for the study. If we just consider the difference of mean in Return on equity of all companies establishes the fact the firm profitability is comparatively better than that of its competitor. Thus the study reveals that the companies chosen for the study were no better than that of the Saud Bahawan group in all the parameters taken for the study. Keywords: financial performance, ROE, EPS & Debt ratio. JEL Classifications: G30, G32, G39